Motor adaptation in complex sports - The influence of visual context information on the adaptation of the three-point shot to altered task demands in expert basketball players - Stöckel, T.; Fries, U. (Journal of Sports Sciences, 2013)
We examined the influence of visual context information on skilled motor behaviour and motor adaptation in basketball. The rules of basketball in Europe have recently changed, such that that the distance for three-point shots increased from 6.25 m to 6.75 m. As such, we tested the extent to which basketball experts can adapt to the longer distance when a) only the unfamiliar, new three-point line was provided as floor markings (NL group), or b) the familiar, old three-point line was provided in addition to the new floor markings (OL group). In the present study 20 expert basketball players performed 40 three-point shots from 6.25 m and 40 shots from 6.75 m. We assessed the percentage of hits and analysed the landing position of the ball. Results showed better adaptation of throwing performance to the longer distance when the old three-point line was provided as a visual landmark, compared to when only the new three-point line was provided. We hypothesise that the three-point line delivered relevant information needed to successfully adapt to the greater distance in the OL group, whereas it disturbed performance and ability to adapt in the NL group. The importance of visual landmarks on motor adaptation in basketball throwing is discussed relative to the influence of other information sources (i.e. angle of elevation relative to the basket) and sport practice.